2005
DOI: 10.1262/jrd.17052
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Motility, Plasma Membrane Integrity, and Binding Capacity to Homologous Zona Pellucida of Cryopreserved Epididymal Spermatozoa in the Domestic Cat

Abstract: Abstract. We examined motility, plasma membrane integrity, and binding capacity to homologous zona pellucidae (ZP) of frozen/thawed epididymal cat sperm as a model species for endangered felines. Epididymal spermatozoa from 20 domestic cats were frozen with freezing egg-yolk extender containing 3.0% glycerol in 0.25-ml straws. Post-thaw motility and plasma membrane integrity of the frozen/thawed spermatozoa were 31.8 ± 2.4% and 32.2 ± 4.2%, respectively. The frozen/thawed spermatozoa were co-cultured with froz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
16
2
Order By: Relevance
“…2006). On the contrary, we obtained better results regarding sperm motility and PMI compared with Kashiwasaki et al. (2005).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…2006). On the contrary, we obtained better results regarding sperm motility and PMI compared with Kashiwasaki et al. (2005).…”
Section: Discussioncontrasting
confidence: 56%
“…Our post-thawing results for control and cooled sperm were lower for sperm motility, progressive status and PMI when compared with other studies using cat epididymal sperm (Axne´r et al 2004;Tebet et al 2006). On the contrary, we obtained better results regarding sperm motility and PMI compared with Kashiwasaki et al (2005). Since freeze-thaw protocols are considerably different among these studies, it is difficult to determine which factors may have influenced post-thaw viability.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been reported that a pregnancy rate of only about 10% was obtained in the domestic cat after the use of frozen-thawed semen with vaginal insemination (Tsutsui et al, 2003). The fertilizing ability of frozenthawed epididymal spermatozoa has been proven (Kashiwazaki et al, 2005). Cryopreservation of epididymal spermatozoa is a potentially valuable procedure for banking genetic resource from individuals of endangered species that die accidentally, (Tsutsui et al, 2003) a conception rate of 27.3% for eleven female cats that received unilateral intrauterine AI of 5 × 10 7 sperm has been reported (Nakatsukasa et al, 2000, Hay & Goodrowe, 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the domestic cat may be used as an important experimental and useful model to establish assisted reproductive technologies in wild cats, such as, for instance, artificial insemination, in vitro fertilization, embryo transfer, and embryo/sperm cryopreservation (Kashiwaki et al, 2005; Pelican et al, 2006; Nagano et al, 2008). However, all these techniques have some limitations once the gametes are terminally differentiated (haploid cells) and are available in a finite number.…”
mentioning
confidence: 99%